Ethnomedicinal Aspects of Sundanese Traditional Homegarden: A Case Study in Rural Sumedang, West Java, Indonesia - Budiawati Supangkat Iskandar; Yayan Suryana; Dede Mulyanto; Johan Iskandar; Rimbo Gunawan (The Ethnobiological Society of Indonesia, 2023)
Rural people of West Java have rich local knowledge on use of plant species to treat various ailments. The traditional medicinal plants have been predominantly cultivated in home-garden agroforestry systems. Nowadays, however, the local knowledge of Sundanese rural people on both ailments and medicinal plants have eroded. In addition, various plants in the homegarden systems have decreased due to conversion of the traditional homegardens to monoculture commercial crops. Rural people in Cibunar, Sumedang, West Java have still strongly maintained Sundanese cultures, including using local knowledge on various ailments and medicinal plants to treat various ailments. This study aimed to elucidate (1) the local knowledge of rural people of Cibunar, Sumedang on illnesses; and (2) role of the homegardens as source of medicinal plants. Method used in this study was mixed-method, qualitative and quantitative with ethnomedicine and ethnobotanical approach. The result of study showed that rural Sundanese community has vernacular names of illnesses, including gering or sakit in Indonesian. Based on local rural people perception, various illnesses can be caused by many factors, poor sleep, bad eating, weather, food poisoning, work fatigue and accidents, including injuries. Treatment of illness according to the local people is usually undertaken by self-treatment, buy medicine from small shops (warung), go to a community health center (Puskesmas), and go to healer (dukun). The traditional agroforestry of homegarden systems have played an important role as sources of medicinal plants, and providing various foods, and resistant with environmental changes, including pests and climate changes.